Combination of fuzzy-AHP and DEMATEL-ANP with GIS in a new hybrid MCDM model used for the selection of the best space for leisure in a blighted urban site - Pourahmad, Ahmad; Hosseini, Ali; Banaitis, Audrius; Nasiri, Hossein; Banaitienė, Nerija; Tzeng, Gwo-Hshiung (Technological and Economic Development of Economy, 2015)
Urban blight issues have transformed over time. Today, the focus is on the social context and such services as recreation and leisure. Considering that the insufficiency of leisure spaces in blighted urban neighbourhoods gives rise to social and cultural problems in Tehran, this research aims to identify the best leisure space in a blighted urban site. The selection process uses the combination of a new hybrid MCDM model and GIS. The integration of GIS and MCDM makes a powerful tool for the selection of the best leisure space in a site because GIS provides efficient manipulation, analysis and presentation of spatial data while MCDM supplies consistent weight of sub-criteria and criteria. The results show the interrelations between dimensions and criteria, also influential priorities and the most important sequences of those. Afterward, this study employs DANP to obtain the weight of each criterion and select a site for leisure using GIS, based on INRM from the DEMATEL method.